Effect of formula factors on the properties of HPMC plant hollow capsule film. (3rd July 2021) - Ding, Huipu; He, Shulei; Luo, Wenqin; Liu, Liping; Wang, Sa; Chen, Xuhan
Abstract: In order to explore the effect of the hollow capsule material formulation on the capsule glue and film formation, this study used hydroxypropylmethylcellulose (HPMC), carrageenan, KCl and Tween 80 as raw materials to determine the production of HPMC hollow capsules suitable formula. The optimal process conditions are as follows: the proportions of HPMC, carrageenan, KCl and Tween 80 in the solvent (purified water) are 18% (m:V), 0.7% (m:V), 0.07% (m:V) and 0.018% (V:V), respectively. Under this condition, the viscosity of the resulting solution, glue solidification temperature and gel strength were medium. The resulting film has low hygroscopicity, good solubility, optical properties and mechanical properties. This research can provide data support for the precise formulation and industrial production of HPMC hollow plant capsules.